The planning of herbs and spices plots as a living laboratory in Universiti Malaysia Sabah, Malaysia - Phuah Mei Xuan; Shahida Mohd Sharif; Izyan Ayuni Mohamad Selamat (Bangladesh Agricultural University Research System (BAURES), 2020)
Campus landscape offers various opportunities to enrich teaching and learning experience to students. It is especially true for an agriculture-based faculty where most of the teaching and learning experience takes place. The living laboratory is one of the emerging trends to support practical and interactive approach that can support project-based learning pedagogic method. Therefore, the study aims to develop a sustainable design framework to establish Herbs and Spices Plot as a living laboratory for teaching and learning purposes in agricultural-based faculties. For this research, the Faculty of Sustainable Agriculture (FSA) has been selected as the case study to help researchers to understand the opportunities and challenges to establish a living laboratory in faculties. An interview has been carried out with an expert to elicit issues and problems surrounding the idea of developing a sustainable design guideline for Herbs and Spices plot in universities. The study employed a questionnaire survey to help researchers to understand the users, which are the students and staff of the faculty. The findings from the questionnaire survey are used to provide guidelines to form the basis in developing a design guideline for Herbs and Spices Plot in agricultural-based faculties. The study also visualises the guideline in 3D form by preparing a Herbs and Spices Plot Master Plan using SketchUp and Lumion software.